PENGARUH PENGARUH PENERAPAN MODEL PBL DAN INQUIRI DENGAN PENDEKATAN CTL TERHADAP KEMAMPUAN HOTS SISWA PADA MATERI SPLDV DIKELAS IX - Rachel Cecilia Simarmata; Nizlel Huda; Roseli Theis (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Balikpapan, 2026)
This study is based on the low level of students' HOTS abilities at SMP Negeri 14 Kota Jambi, as well as the continued dominance of conventional teaching models. Based on this, the purpose of this study is to examine the use of Problem-Based Learning (PBL) and inquiry learning models combined with a contextual teaching and learning to improve ninth-grade students’ HOTS skills on the topic of Systems of Linear Equations in Two Variables. The research employed a posttest control group design. All ninth-grade classes constitute the population in this study. The samples included class IX F, which was taught using the PBL model with a real-life-based approach; class IX E, which used the inquiry learning model with a real-life-based approach; and class IX D as the control class, which applied a conventional learning model. Data were collected through observation sheets to assess the implementation of teacher and student activities, as well as through a posttest instrument measuring HOTS abilities. The results showed differences among the classes using the PBL model with a real-life-based approach, the inquiry model with a real-life-based approach, and the conventional model. The average posttest scores in the experimental classes I and II were 6.25 and 6.43 (high), while the control class only achieved an average score of 1.96 (low).